2021
DOI: 10.1016/j.isci.2021.103003
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic nuclear receptors coordinate energy metabolism to regulate Sox9+ hepatocyte fate

Abstract: Summary Recent research has indicated the adult liver Sox9 + cells located in the portal triads contribute to the physiological maintenance of liver mass and injury repair. However, the physiology and pathology regulation mechanisms of adult liver Sox9 + cells remain unknown. Here, PPARα and FXR bound to the shared site in Sox9 promoter with opposite transcriptional outputs. PPARα activation enhanced the fatty acid β-oxidation, oxidative phosphorylation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…In recent years, the role of Sox9 + hepatocytes in chronic liver injury repair has been widely documented [ 10 , 38 ], but the role of Sox9 + hepatocytes in acute liver injury repair has rarely been reported. Hepatic IRI model was applied to investigate the function of Sox9 + hepatocytes in acute liver injury repair.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the role of Sox9 + hepatocytes in chronic liver injury repair has been widely documented [ 10 , 38 ], but the role of Sox9 + hepatocytes in acute liver injury repair has rarely been reported. Hepatic IRI model was applied to investigate the function of Sox9 + hepatocytes in acute liver injury repair.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Font-Burgada et al have found that Sox9 is also expressed in a subset of hepatocytes, and Sox9 + hepatocytes are present around the ductal plate, and they are also known as hybrid hepatocytes (HybHP), because they jointly express cholangiocyte-specific marker CK19 and key hepatocyte marker HNF4α, and they proliferate extensively in response to chronic hepatocyte-depleting injuries [ 9 ]. Our previous studies indicate that Sox9 + hepatocytes can serve as bipotent progenitors to repair the liver after chronic liver injury [ 10 , 11 ]. However, the role and mechanism underlying the Sox9 + hepatocytes in response to the acute liver injury have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of Primary Mouse Hepatocytes and Cell Sorting: Primary mouse hepatocytes were isolated by the previously reported method with minor modification. [46] Briefly, the WT and LKO mice were anesthetized with Avertin (Sigma-Aldrich, T48402, 240 mg kg −1 ) by intraperitoneal injection, and the hepatic portal vein was cannulated. The liver was perfused at 6 mL min −1 with pre-warmed perfusion medium containing EGTA for 8 min.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, this facilitates the regeneration of Sox9+ hepatocytes that assume the role of bidirectional progenitor cells following liver injury. These cells can give rise to hepatocytes or bile duct cells, contributing to liver repair and regeneration [ 149 , 150 ]. Furthermore, specific FXR knockout in hepatocytes significantly delays the initiation signal of growth factors, hampering liver regeneration [ 151 ].…”
Section: Pharmacology Of Fxr In Liver Fibrosismentioning
confidence: 99%